Risques connus et impact de mesures prises sur ces risques en transfusion sanguine - Garraud, Olivier (Transfus Clin Biol, 2011)
Transfusion is indeed associated with risks that are diverse in nature. Besides, the society expects a risk- and vice-exempt transfusion. During the recent past years, there have been three levels of safety implementation in transfusion: a generalized risk assessment policy; a mastering of processes; standard quality engineering. However, these safety measures have impacts in several ways, such as management and organization, inventory, economics and possibly ethics. All these issues are addressed in the present essay as well as the possible effect of pathogen reduction procedures.